HUBUNGAN RELATIONSHIP MARKETING, CUSTOMER SATISFACTION DAN CUSTOMER LOYALTY - Nia Rohmatin Nikmah (Universitas Trunojoyo Madura, 2017)
Relationship marketing is a customer-based strategy. Maintaining and providing optimal service to customers is an implementation of relationship marketing strategy. Relationship marketing has an influence in shaping customer satisfaction. From customer satisfaction will create a loyalty. Of the several references examined found some opinions about the dimensions of relationship marketing theory. The theory evolved its diversity from year to year.